2020
DOI: 10.48550/arxiv.2009.05036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intertwined Magnetic Dipolar and Electric Quadrupolar Correlations in the Pyrochlore Tb$_2$Ge$_2$O$_7$

A. M. Hallas,
W. Jin,
J. Gaudet
et al.

Abstract: We present a comprehensive experimental and theoretical study of the pyrochlore Tb 2 Ge 2 O 7 , an exemplary realization of a material whose properties are dominated by competition between magnetic dipolar and electric quadrupolar correlations. The dipolar and quadrupolar correlations evolve over three distinct regimes that we characterize via heat capacity, elastic and inelastic neutron scattering. In the first regime, above T * = 1.1 K, significant quadrupolar correlations lead to an intense inelastic mode t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…Inelastic neutron scattering experiments showed that the first excited CEF mode becomes dispersive below about 20 K, suggesting CEF levels among adjacent Tb 3+ ions are interacted [29,36]. Moreover, in a sister compound Tb 2 Ge 2 O 7 , recent comprehensive study showed that significant correlations between quadrupolar moments of Tb 3+ ions are present above 1.1 K [37]. All these suggests that the onset of quadrupolar correlation is much higher than the longrange quadrupolar ordering temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Inelastic neutron scattering experiments showed that the first excited CEF mode becomes dispersive below about 20 K, suggesting CEF levels among adjacent Tb 3+ ions are interacted [29,36]. Moreover, in a sister compound Tb 2 Ge 2 O 7 , recent comprehensive study showed that significant correlations between quadrupolar moments of Tb 3+ ions are present above 1.1 K [37]. All these suggests that the onset of quadrupolar correlation is much higher than the longrange quadrupolar ordering temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the other lanthanide ions presented so far, the non-Kramers doublet of the J=6 free-ion ground state manifold of Tb 3+ is separated from its first excited doublet by only ∼1.4 meV [2,64,176,[312][313][314]. Corresponding to a gap roughly an order of magnitude smaller than Yb 3+ , the application of the pseudospin-1/2 model is not necessarily straightforward, necessitating the incorporation of more subtle effects, possibly even on equal footing with ĤCEF [315][316][317]. Such subtle effects include virtual crystal field transitions, secondary corrections that introduce anistropic exchange and may potentially stabilize a quantum spin ice ground state in the cooperative paramagnet Tb 2 Ti 2 O 7 [176,268,315,316,[318][319][320].…”
Section: Dynamic Magnetic Ground States: Yb2insbo7 Tb2insbo7 and Sm2i...mentioning
confidence: 99%
“…More recently, direct measurement of the CEF levels in MgHo 2 Se 4 via inelastic neutron scattering reveals a non-Kramers doublet ground state, in close proximity to an excited doublet and singlet below 1 meV, and yet another singlet below 3 meV [50]. The complicated CEF scheme with many low lying levels bares some resemblance to the terbium oxide pyrochlores, whose ground states are formed by two closely spaced doublets and the competing energy scales of single ion effects and the ion-ion interactions leads to rich and complex physics that has eluded description by a microscopic theory [72][73][74][75]. In the holmium spinels the lowest lying excited CEF levels are even more numerous and closely spaced than the 1.5 meV level in the terbium pyrochlores, and thus we can expect similarly rich physics.…”
Section: Holmium Chalcogenide Spinelsmentioning
confidence: 99%